Applying Bioinformatic Tools for Modeling and Modifying Type II E. coli l-Asparginase to Present a Better Therapeutic Agent/Drug for Acute Lymphoblastic Leukemia. - Mahboobi, Mahdieh; Sedighian, Hamid; Hedayati C. H., Mojtaba; Bambai, Bijan; Soofian, Saeed Esmaeil; Amani, Jafar (International Journal of Cancer Management, 2017)
Background: Asparginase is known to be one of the most important bedrocks of acute lymphoblastic leukemia (ALL) treatment in almost all pediatric regimens in treatment protocols. Escherichia coli L-Asparginase (EC 3.5.1.1) is one of the most common resources to produce this enzyme. One of the affordable methods to overcome the side effects of drug is utilizing bioinformatic tools in the form of In silico study. In this study we designed a new structure of L-Asparginase to decrease its toxicity, reduce some side effects and increase the stability. Methods:We usedsomebioinformatics software and servers like Toxin red, Popmusic, kobami and I-TASSER server to reduce toxicity level of enzyme, and to increase stability and enzyme half-life. Results:We obtained 6 protein sequences in which the best was Mut 6 with four changes in structure: L23G, K129L, S263C and R291F. In contrast to the wild type, the new predicted protein is not toxic and has 25 hours more half-life and 600 kcal/mol more stable with no significant change in protein secondary, tertiary structure, antigenicity and allergenicity. Conclusions: Finally, sequence number 6 was the only sequence with all distinct characteristics: non-toxic, more stability and more half life.